PENGEMBANGAN MEDIA MOBUIN BERBASIS BUDAYA LOKAL SUMATRA UTARA PADA MATERI INDONESIAKU KAYA BUDAYA KELAS IV SD - Nurmairina, Dea; Nurmairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce a learning media product and determine the validity and practicality of developing monopoly media on the material "My Indonesia is rich in culture" which is motivated by a lack of innovation in learning media, making students less active in the learning process. This research is a type of development research (R&D). This research was developed using the five steps of the ADDIE development model, namely 1) analyze, 2) design, 3) development, 4) implementation, 5) evaluation. Data collection techniques used were interviews, observation and questionnaires. Quantitative and qualitative data were analyzed using a Likert scale. This research produces learning media in the form of monopoly learning media based on the local culture of North Sumatra in science and science learning for class IV elementary school with the material "My Indonesia is rich in culture". Based on validation carried out by material experts, it produced a score of 38 with a percentage of 95%, media experts produced a score of 49 with a percentage of 94% and practicality produced a score of 55 with a percentage of 92% in the "very good" category. The validation results show that the learning media product is worthy of being tested on students. The results of the field trials produced a score of 560 with a percentage of 87.5 in the "very good" category. Thus, the monopoly learning media product based on the local culture of North Sumatra in science and science learning for grade IV elementary school, the material "My Indonesia is rich in culture" created by researchers is suitable for use in the science and science learning process.